The influence of digital promotion and brand image on customer purchasing interest mediated by consumer satisfaction (case study of Mobilku WOM Finance product, Lubuk Linggau Branch) - purnando, Hengki; Saparso, Saparso (Enrichment : Journal of Management, 2025)
This study aims to analyze the effect of digital promotion and brand image on customer purchase intention, with consumer satisfaction as a mediating variable, in the context of the Mobilku product at PT WOM Finance Lubuk Linggau Branch. The background of this research is based on the increasingly intense competition in the financing industry, where digital promotion strategies and brand image strengthening are crucial factors in attracting consumer attention. However, sales achievements at the research branch showed fluctuations, indicating that marketing strategies were not yet optimal; therefore, consumer satisfaction needs to be considered as a mediating factor between promotion, brand image, and purchase intention. This research employs a quantitative method with a survey approach. The study population consisted of 547 active customers of WOM Finance Lubuk Linggau Branch, from which a sample of 230 respondents was determined using Slovin’s formula and selected through simple random sampling. Data were collected using a Likert-scale questionnaire, and analyzed with Partial Least Square–Structural Equation Modeling (PLS-SEM) using SmartPLS software. The findings reveal that digital promotion has a positive effect on consumer satisfaction but does not have a direct significant effect on purchase intention. Brand image has a positive effect on both consumer satisfaction and purchase intention. Consumer satisfaction significantly affects purchase intention and mediates the relationship between digital promotion and brand image toward customer purchase intention.